2021
DOI: 10.15252/emmm.202114314
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive progestins with androgenic properties stimulate breast epithelial cell proliferation

Abstract: Hormonal contraception exposes women to synthetic progesterone receptor (PR) agonists, progestins, and transiently increases breast cancer risk. How progesterone and progestins affect the breast epithelium is poorly understood because we lack adequate models to study this. We hypothesized that individual progestins differentially affect breast epithelial cell proliferation and hence breast cancer risk. Using mouse mammary tissue ex vivo, we show that testosterone-related progestins induce the PR target and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 65 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…The other progestins did not change tumour size or metastatic burden. It has been suggested that only progestins with androgenic effects stimulate the proliferation of mammary gland cells 49 . In this model, levonorgestrel which is also an androgen‐derived progestin as MPA, was not as stimulatory as MPA.…”
Section: Discussionmentioning
confidence: 67%
“…The other progestins did not change tumour size or metastatic burden. It has been suggested that only progestins with androgenic effects stimulate the proliferation of mammary gland cells 49 . In this model, levonorgestrel which is also an androgen‐derived progestin as MPA, was not as stimulatory as MPA.…”
Section: Discussionmentioning
confidence: 67%
“…Nevertheless, these observations are in contrast with the findings that contraceptive progestins with androgenic activity, such as the T-related and widely used levonorgestrel, promote hyperproliferation of the breast epithelium with cytological changes, in a xenograft model obtained through intraductal injection of human mammary cells expressing hormone receptors [ 86 ]. Though limited by the fact that the hormonal milieu of human breast epithelial cells in mice is quite different to that in humans, these findings are consistent with a prospective study, involving 1,359,323 p-y from 1978 to 2002, that revealed an increased risk of IBC in postmenopausal women receiving estrogen/androgen hormone therapies compared with patients treated with estrogens alone [ 87 ].…”
Section: Exogenous Androgen Exposure and Breast Cancer Incidencementioning
confidence: 77%
“…Included normal breast tissue was obtained from women undergoing mammoplasty surgery with no previous history of BC, who gave informed consent, and the tissue samples were examined by the pathologist to be free of malignancy and processed as described 24 . The study was approved by the Cantonal ethics committee, Commission Cantonale d’éthique de la recherche sur l’être humain, CER-VD, Avenue de Chailly, 1012 Lausanne, Switzerland (Approval number 183/10).…”
Section: Methodsmentioning
confidence: 99%